Singapore : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Singapore's economy continues to perform well despite being hit by a combination of cyclical and structural factors, originating both at home and abroad. Growth moderated from 3.3 percent in 2014 to 2 percent in 2015, and it was 2.2 percent in the first half of 2016. Unemployment has remained low, but net employment generation slowed rapidly in 2015, and headline inflation has stayed below zero since late 2014. Growth is projected to moderate slightly to 1.7 percent in 2016 as the full impact of the global shocks experienced in 2015 is felt, and is expected to recover to 2.2 percent in 2017.